Relative Efficiency of Latin Square Design on Natural Grasslands in Agra Ravines - Babu, Ram; Aggarwal, M C; Kumar, Nirmal; Puri, D N (Annals of Arid Zone, 2016)
The efficiency of various Latin Square Designs (LSD) relative to the Complete Randomised Designs (CRD) and Randomised Complete Block Designs (RCDD) for various sizes and shapes of plots on natural grasslands of Agra ravines was worked, out. The relative efficiencies (percentage) of 3x3. 4x4. 5x5 and 6x6 LSD for different plot sizes and shapes were compared with CRD and RCBD. when rows were trcated as blocks (ignoring columns) and whcn columns were treated as blocks (ignoring rows) have been computed. Thc number of units rcquired in CRD and RCBD taking rows as blocks or columns as blocks for obtaining thc relative efficiency equivalent to that of 3x3 to 6x6 LSD were also evaluated and it was found that LSD was more efficient than CRD and RCBD for experimentation with natural grasslands having more than 10% slope.